Correlation of previous experience, patient expectation and the number of post‐delivery adjustments of complete dentures with patient satisfaction in a Brazilian population. (12th May 2013) - Gaspar, M. G.; Dos Santos, M. B. F.; Dos Santos, J. F. F.; Marchini, L.
Summary A number of variables may influence the outcome of complete denture therapy. The objective of this study was to verify possible correlations between previous experience with dentures, patient expectation and the number of post‐delivery adjustments with patient satisfaction after treatment. One hundred patients (mean age 61·9 ± 10·3) rated their previous experiences with complete dentures and their expectations before and satisfaction after treatment on a visual analogue scale (VAS) using scores from 0 (worst results) to 10 (best results). The number of post‐delivery adjustments and other patient‐related clinical variables was also noted. Patient expectation scores were higher than previous experience scores and satisfaction after treatment scores. Positive and weak correlations were found between previous chewing experiences with complete dentures, with regard to chewing expectations and comfort of use. Phonetics and comfort of use in previous experiences presented a positive correlation with expectations for chewing, aesthetics, phonetics and comfort of use. Groups of patients with different levels of education presented significant differences in expectation scores regarding comfort of use as well. A negative and weak correlation was found between phonetics satisfaction and the number of post‐delivery adjustments. Patients' expectations for the therapy were higher than their satisfaction after treatment. Previous experiences with complete dentures could slightly influence patients' expectations and satisfaction, whereas lower scores for previous experience with complete dentures caused lower scores for both expectation and satisfaction. Patients' educational levels and the number of post‐delivery adjustments influenced negatively the expectations about comfort of use and patient satisfaction, respectively.